Sosialisasi Penyuluhan Hukum Tentang Bahaya Narkotika Bagi Kalangan Remaja Di SMPN 2 Wanayasa Kabupaten Purwakarta - Rizki Mohamad Eka Marsa Sadjat (Pusat Riset dan Inovasi Nasional, 2023)
The problem of narcotics in Indonesia is still something that is urgent and complex. In the last decade this problem has become widespread. Evidenced by the significant increase in the number of narcotics abusers or addicts, as the disclosure of narcotics crime cases increases, the pattern is increasingly diverse and the syndicate network is increasingly massive. The Indonesian people, and even the world community, in general, are currently facing a very worrying situation due to the widespread illegal use of various types of narcotics. This concern is getting sharpened due to the rampant illicit trafficking of narcotics which has spread to all levels of society, including among the younger generation. This will greatly affect the life of the nation and state in the future. The behavior of some teenagers who have clearly ignored the values, norms and laws that apply in people's lives is one of the reasons for the rampant use of narcotics among the younger generation. In everyday life in the midst of society there are still many teenagers who still abuse narcotics.